Binding 13, part 1 eaudiobook - Walsh, Chloe (Boys of Tommen, 2019)
His first, last, and only true love has always been rugby. Until now. She's damaged. He's determined. Fate brought them together. Love binds them. Johnny Kavanagh has everything going for him. On the rugby pitch, he's a force to be reckoned with. Primed for stardom, he's heading straight for the top. Nothing can possibly get in his way, right? Not even the shy new girl at Tommen College. The one with the sad eyes and hidden bruises. The one that distracts him like no one ever has. Plagued with a hidden injury and desperate to impress the scouts watching his every move, Johnny has been placed on a pedestal so high, he has no room to make mistakes. Johnny needs to keep his head in the game. He needs to stay focused and cannot afford to let distractions get in the way of the big picture. But what happens when a lonely girl with sad eyes becomes the only picture? Two teenagers from opposite sides of the tracks collide in the first audio instalment of Binding 13. Based in Ireland, the Boys Of Tommen series is bound to captivate and lure you into the world of rugby, love, and teenage heartbreak.